PERAN KEPERCAYAAN PADA PENGAWAS MEMEDIASI PENGARUH PEMBERDAYAN KARYAWAN TERHADAP PERILAKU KERJA INOVATIF - Cahyani, Ni Nyoman Surya; Indrawati, Ayu Desi (E-Jurnal Manajemen; Vol 7 No 11 (2018), 2018)
Innovative work behaviors are behaviors that include exploration of new idea ideas, which also include implementing new ideas, applying new knowledge and efforts to achieve personal or business performance improvements to the company . The aim of this researchmis to determine the influence of  employee empowerment on Trust in supervisor and innovative work behaviour in Bale Udang Mang Engking  Ubud. This research is conducted on Bale Udang Mang Engking  Ubud. The population in this research is all of the employees in Bale Udang Mang Engking  Ubud. The total population sampling method is used, which results in a total of 74 sample. The data collection method is conducted by interviews and distributing questionnaires. The analysis technique utilized is the path analysis. In this research, the sobel test is used to detect the mediating variable, which is trus in supervisor . The research result shows that employee empowerment has positive and significant influence on trust in supervisor. Employee Empowerment has positive and  significant influence on trust in supervisor. Trust in supervisor has positive and  significant influence on innovative work behaviou. Furthermore, Trust in supervisor is accepted as an intervening variable in mediating the employee empowerment on innovative work behaviour.